Improvement of Bachelors' Professional Mathematical Competence in the Field of Modeling for Oil and Gas industry - Kozlov, Anatoly; Tamer, Olga; Lapteva, Svetlana (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The study is devoted to improving the professional training of students in the field of mathematical modeling in the oil and gas industry. Deeper integration into the training of modern statistical methods and models is used to improve the educational efficiency and develop mathematical models of technological processes of the oil and gas industry. To test the proposed models, a pedagogical experiment with 189 students aged 19 to 21 is performed. The research is based on the November Institute of Oil and Gas in the Yamalo-Nenets Autonomous District. The outcomes of training under the new program are evaluated at three levels of competency formation in accordance with the university’s assessment systems. This approach ensures a level playing field for all respondents. The relevance of improving the competence of students in the field of mathematics is proved through the increase in grades at all three levels of competency formation. The study describes in detail the system of profile differentiation of the mathematical training, which is based on a modular competency approach and compares various approaches and methods of professional competence formation among oil and gas workers.